Contestation of Islamic Discourses: Responses of West Sumatra Scholars to Contemporary Religious Discourses - Saputra, Riki; Arrasyid, Arrasyid; Ritonga, Mahyudin (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2023)
This study aimed to elucidate Islamic discourses and the responses of scholars, particularly in West Sumatra, to contemporary religious issues. A qualitative and a socio-anthropological method was adopted. The result showed that the tug-of-war in religious discourses in West Sumatra was both negotiating and confrontational with a dynamical and sharply dialectical religious discourse. In West Sumatra where religion was considered as life philosophy, scholars were placed in a highly central position in confronting the dynamics in the community. Consequently, the responses of scholars were significant and transformative with substantial strength.